2014
DOI: 10.1186/1471-2458-14-1136
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence against women in Eastern Sudan

Abstract: BackgroundViolence against women is one of the major public health problems in both developed and developing worlds. The aim of this study was to investigate the prevalence of current (occurred in one year preceding the survey) domestic violence and socio-demographic factors associated with domestic violence against women.MethodsThis was a cross sectional household survey (face to face interview) conducted in Kassala, eastern Sudan, from 1st March to 1st June 2014. Multivariable analyses were performed, Confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
42
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 9 publications
16
42
1
1
Order By: Relevance
“…1,9,38 The findings of this study highlight the importance of public awareness regarding physical violence against women, as well as preventive measures for maxillofacial injuries. As observers, professionals working in primary health care are in a unique position to detect, treat, and refer victims to institutions that can offer specialized assistance.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…1,9,38 The findings of this study highlight the importance of public awareness regarding physical violence against women, as well as preventive measures for maxillofacial injuries. As observers, professionals working in primary health care are in a unique position to detect, treat, and refer victims to institutions that can offer specialized assistance.…”
Section: Discussionmentioning
confidence: 68%
“…1 Injuries to the head, face, or neck seem to be suggestive and not specific markers of interpersonal physical violence, demonstrating that a full examination of the victim is essential in the investigation of this problem. In developing countries, the high prevalence of violence seems to be associated with low socioeconomic conditions of the population and to the rules of social interaction that implicitly encourage women to accept the different behaviors of men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Violence in the family environment accounts for a significant proportion of the morbidity and mortality rates in Brazil We found that adolescents and adults (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and 20-59 years old) are the age groups at risk for DV. Violence against adolescents and young adults is an important cause of early mortality and reduced life quality 25 .…”
Section: Discussionmentioning
confidence: 92%
“…Sexual violence, either by intimate partners or not, is widespread, mainly affecting women worldwide [6][7][8] . In Brazil, as in other countries, most violent episodes are related to alcohol abuse, illicit drug use, and access to weapons 9,10 . Not only women, but also children and elderly, are most at risk of being domestic violence (DV) victims.…”
Section: Introductionmentioning
confidence: 99%